1996
DOI: 10.1063/1.872007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variable x-ray preheat shielding in indirectly driven implosions

Abstract: Hard x-ray (>100 keV) imager to measure hot electron preheat for indirectly driven capsule implosions on the NIFa) Rev. Sci. Instrum. 83, 10E508 (2012); K and Lshell xray spectroscopy of indirectly driven implosions (invited) Rev. Sci.The performance of indirectly driven fusion capsules has been improved by mid Z doping of the plastic capsule ablator. The doping increases x-ray preheat shielding leading to a more isentropic compression, higher convergence, and higher neutron yield. A 4ϫ increase in neutron yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Landen et al 12 reported temperatures 30% greater than calculated for indirectly driven capsule experiments performed on the Nova laser. 21 Despite the increased observed ion temperature, the simulated yield was 3-4 times the observed yield.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Landen et al 12 reported temperatures 30% greater than calculated for indirectly driven capsule experiments performed on the Nova laser. 21 Despite the increased observed ion temperature, the simulated yield was 3-4 times the observed yield.…”
Section: Discussionmentioning
confidence: 95%
“…In inertial confinement fusion (ICF) experiments, 6,7 this distribution is usually measured 8 in the neutron time-of-flight domain using scintillation detectors operated in current mode 9 or neutron detector arrays, 10 but has also been measured using proton or other charged-particle recoil methods. 11 Neutron spectral widths from ICF experiments have often been observed to be wider than expected from simulations [12][13][14] or the measured yield. 15 This has been attributed to mass flows within the reacting region, 15,16 higher contributions to the spatially averaged ion temperature from the hottest central regions of the core, 12 and expansion of the reacting plasma at velocities near the sound speed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to control the deposition of energy in the ablator, and thus the shock compression of the fuel, mid-Z ablator dopants such as germanium, bromine, or copper are often added to the low-Z ablator material. 1,2 The increased opacity provided by ablator dopants ͑see Fig. 1͒ serves to change the radiation-matter coupling as well as to shield the fuel from preheat.…”
Section: Introductionmentioning
confidence: 99%
“…[This stage has previously been investigated in indirectly driven targets at the Lawrence Livermore National Laboratory (LLNL) using plastic targets with an inner layer of Ti-doped CH and an Ardoped D 2 fill. [6][7][8] ] The goal of our initial experiments was to ensure that our diagnostics could measure the conditions in both the core and the shell during shell deceleration and stagnation and that they had enough sensitivity to observe differences in core conditions under various RT-growth conditions. The RT growth was modified by varying the temporal pulse shape (Gaussian or square) and by doping the outer 6 µm of the CH shell with chlorine.…”
Section: Measurements Of Core and Pusher Conditions In Surrogatementioning
confidence: 99%